Cohort event monitoring of safety of COVID-19 vaccines: the Italian experience of the “ilmiovaccinoCOVID19 collaborating group” - Luxi, Nicoletta; Bellitto, Chiara; Ciccimarra, Francesco; Cappello, Emiliano; L’Abbate, Luca; Bonaso, Marco; Ajolfi, Chiara; Baldo, Paolo; Bonaiuti, Roberto; Costantino, Claudio; De Sarro, Giovambattista; Di Mauro, Cristina; et al. (Frontiers in Drug Safety and Regulation, 2024)
In 2021, the European Medicines Agency supported the "Covid Vaccine Monitor (CVM)," an active surveillance project spanning 13 European countries, aimed at monitoring the safety of COVID-19 vaccines in general and special populations (i.e., pregnant/breastfeeding women, children/adolescents, immunocompromised, people with a history of allergies or previous SARS-CoV-2 infection). Italy participated to this project as a large multidisciplinary network called "ilmiovaccinoCOVID19 collaborating group" Methods: The study aimed to describe the experience of the Italian network "ilmiovaccinoCOVID19 collaborating group" in the CVM context from June 2021 to February 2023. Comprising about 30 partners, the network aimed to facilitate vaccinees' recruitment. Participants completed baseline and follow-up questionnaires within 48 hours from vaccination over a 6-month period. Analyses focused on those who completed both baseline and the first follow-up questionnaire (Q1), exploring temporal trends, vaccination campaign correlation, and loss to follow-up. Characteristics of recruited vaccinees and vaccinee-reported adverse drug reactions (ADRs) were compared with passive surveillance data in Italy. Results: From June 2021 to November 2022, 22,384,663 first doses and 38,207,452 booster doses of COVID-19 vaccines were administered in Italy. Simultaneously, the study enrolled 1,229 and 2,707 participants for the first and booster doses, respectively. Of these, 829 and 1,879 vaccinees respectively completed both baseline and at least the Q1 and were included in the analyses with a significant proportion of them (57.8%/34.3%) belonging to special cohorts. Most vaccinees included in the analyses were females. Comirnaty® (69%) and Spikevax® (29%) were the most frequently administered vaccines. ADR rates following Comirnaty® and Spikevax® were higher after the second dose, particularly following Spikevax®. Serious ADRs were infrequent. Differences were observed in ADR characteristics between CVM and Italian passive surveillance.Conclusions: This study confirmed the favorable safety profile of COVID-19 vaccines, with findings consistent with pivotal clinical trials of COVID-19 vaccines, although different proportions of serious ADRs as compared to spontaneous reporting were observed. Continuous evaluation through cohort event monitoring studies provides real-time insights crucial for regulatory responses. Strengthening infrastructure and implementing early monitoring strategies are essential to enhance vaccine safety assessment and prepare for future pandemics.